Update and trends on pharmacokinetic studies in patients with impaired renal function: practical insight into application of the FDA and EMA guidelines. Issue 3 (4th March 2017) - Paglialunga, Sabina; Offman, Elliot; Ichhpurani, Nita; Marbury, Thomas C.; Morimoto, Bruce H.
ABSTRACT: Introduction: The incidence of kidney dysfunction increases with age and is highly prevalent among patients with hypertension. Since many therapeutic compounds are primarily eliminated through the kidneys, impaired renal function can have negative consequences on drug disposition, efficacy and safety. Therefore, regulatory agencies such as the Food and Drug Administration (FDA) and European Medicines Agency (EMA) have issued detailed guidelines for new drug applications to determine posology requirements for patients with renal impairment. Areas covered: The current review highlights and contrasts agency requirements for pharmacokinetic renal impairment clinical studies. While many of the guidelines are similar among the two agencies, glomerular filtration rate (GFR) determination and reporting differ. Design considerations for a reduced, full or dialysis renal impairment study, as well as modifications to the FDA's draft guidance are discussed. Furthermore, scenarios where pharmacokinetic modelling analysis can benefit a drug development program are also reviewed. Moreover, practical solutions for patient recruitment challenges are addressed. Expert commentary: We summarize how 'one size does not fit all' for GFR assessment, and recommend when to use certain modalities. Finally, we highlight the need for the pharmaceutical industry to engage therapeutic experts to assist in protocol development for renal impairment studies, as these experts understand the nuances of this special population and recommended guidelines.